1984
DOI: 10.1177/030089168407000510
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Receptors and Breast Cancer: Correlations with Clinical and Histologic Features

Abstract: The possible relationships between hormone receptor status and several clinical (age, gynecologic history, clinical stage) and morphologic aspects (histologic grade, vascular invasion, lymphocytic infiltration, necrosis, fibrosis, elastosis and lymph node metastasis) were evaluated. A highly significant correlation between estrogen receptor levels, patient age, menses regularity and postmenopausal status was found. The histologic features most significantly related to tumor receptor status were histologic grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
1
7

Year Published

1988
1988
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
1
1
7
Order By: Relevance
“…Several studies have reported similar association [ 15 , 18 , 27 ]. Finally, our results do not confirm earlier studies in which the expression of ER was associated with the nature of the presence of lymphocytes in the vicinity of the tumour [ 57 , 58 ]. We chose to examine the nature of the presence of tumour lymphocytes as one of the tumour characteristics that we examined in this study, since such a characteristic could provide an insight into the immunological status of the tumour.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have reported similar association [ 15 , 18 , 27 ]. Finally, our results do not confirm earlier studies in which the expression of ER was associated with the nature of the presence of lymphocytes in the vicinity of the tumour [ 57 , 58 ]. We chose to examine the nature of the presence of tumour lymphocytes as one of the tumour characteristics that we examined in this study, since such a characteristic could provide an insight into the immunological status of the tumour.…”
Section: Discussioncontrasting
confidence: 99%
“…Prior analyses of the effect of age and menopausal status on the expression of prognostic or predictive markers in breast carcinomas have been limited in the factors assessed; however, studies have demonstrated that breast carcinomas in younger or premenopausal women are more likely to exhibit biologic and prognostic features that are known to be associated with a high histologic grade, such as an absence of steroid hormone receptors, 31,42 , a high rate of proliferation 43 and abnormalities in p53 protein. 8,24 -26 It has been hypothesized that this adverse pattern of prognostic indicators and the poorer clinical outcome of younger, premenopausal patients were secondary to the greater proportion of higher grade carcinomas found in these women.…”
Section: Discussionmentioning
confidence: 99%
“…Γπάρχουν βέβαια και οι ερευνητές εκείνοι, που• υποστηρίζουν ότι δεν υ πάρχει 1 καμμ,ία συσχέτιση μεταξύ του ιστολογικού• τύπου και-των υποδοχέων ' (Terenius, et al, 1974, Miïïis, 1980, Fisher, et al, 1981, Nishimura, et al, 1981, Tulusan, et al, 1982, Montesco, et al, 1984, ή καταλήγουν σε μία σχετική έλλειψη συσχέτισης μεταξύ των δύο παραμέ τρων ÇMcCarty, et al, 1980).…”
Section: ιστολογικός τύπος του όγκου και υποδοχείς οιστρογόνωνunclassified
“…Ελάχιστοι μόνο μελετητές δεν έχουν βρει καμμία συσχέτιση, μεταξύ των δύο παραμέτρων , Howat, et al, 1983, Νέκρωση και υποδοχείς οιστρογόνων Η έκταση της νέκρωσης του όγκου εμφανίζει επίσης μία αντιστρόφως ανάλογη συσχέτιση με τη συγκέντρωση• των υποδοχέων. Όγκοι, στους οποίους δεν ανευρίσκονται νεκρώσεις ή όπου αναγνωρίζονται μόνο περιορισμένες εστίες νέκρωσης, είναι πιο συχνά θετικοί για υποδοχείς οιστρογόνων (Fisher, et al, 1980, Montesco, et al 1984.…”
Section: λεμφοκυτταρική διήθηση του στρώματος και υποδοχείς οιστρογόνωνunclassified
See 1 more Smart Citation